Influence of Doping and Annealing on Structural, Optical and Electrical properties Amorphous ZnO Thin Films Prepared by PLD - Azhar AbduAlwahab Ali; K.T. Al-Rasoul; Issam M. Ibrahim (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2015)
The optical gap of the films was calculated from the curve of absorption coefficient (αhע)2 vs. hע and was found to be 3.8 eV at room temperature, and this value decreases from 3.8 to 3.58 eV with increasing of annealing temperature up to 473-673 K, and increases with the Ga doping. λ cutoff was calculated for ZnO and showed an increase with increasing annealing temperature and shifting to longer wavelength, while with doping the λcutoff shifted to shorter wavelength. The photoluminescence (PL) results indicate that the pure ZnO thin films grown at room temperature show strong peaks at 640 nm , but  GaO doped ZnO films showed a band emission in the yellow-green spectral region (380 to 450nm).